Occurrence of Bacterial and Protozoan Pathogens in Red Foxes (Vulpes vulpes) in Central Italy - Valentina Virginia Ebani; Chiara Trebino; Lisa Guardone; Fabrizio Bertelloni; Giulia Cagnoli; Simona Nardoni; Emily Sel; Emily Wilde; Alessandro Poli; Francesca Mancianti (Animals, 2022)
Most surveys of pathogens in red foxes (Vulpes vulpes) have focused on particular agents. The aim of this study was to verify, with bacteriological and molecular analyses, the occurrence of the main bacterial and protozoan pathogens that are able to infect canids, in red foxes regularly hunted in Central Italy. Spleen, brain, kidney and fecal samples from red foxes were submitted to bacteriological and/or molecular analyses to detect Salmonella spp., Yersinia spp., Listeria monocytogenes, Brucella spp., Ehrlichia canis, Anaplasma phagocytophilum, Coxiella burnetii, Leptospira spp., Neospora caninum, Hepatozoon canis, Babesia spp. and microsporidia. Two (9.1%) strains of Yersinia enterocolitica biotype 1 and 2 (9.1%) of Yersinia frederiksenii were isolated from 22 fecal samples. Among the 22 spleen samples, seven (31.8%) were PCR-positive for H. canis and 3 (13.6%) for Babesia vulpes. Kidneys from two (2.9%) foxes, among 71 tested, were PCR-positive for L. interrogans. Even though the analyses were carried out on a small number of animals, the results suggested that red foxes from the selected geographic area may act as reservoirs of some investigated pathogens.